ESTRATEGIAS DE APRENDIZAJE - NIDIA ANGELICA VIVAS LOPEZ (Universidad Distrital Francisco José de Caldas, 2010)
The present text has as objective to make a conceptual approximation to the "learning strategies", to understand how the fact of recognizing and systematizing them will originate fundamental changes in any learning-teaching- evaluating process. To analyze "learning strategies" through the cognitive and interactive perspective makes possible to find different ways to conceive, apply, systematize and evaluate principles that will make easier the optimization of the learning environment, and the teacher job qualification.